CAROTID ARTERY STENTING OF INTERNAL CAROTID ARTERYâ€œNEAR OCCLUSIONâ€ STENOSIS â€“ CASE REPORT - Bushljetikj, Oliver; Zdravkovski, Igor; Manev, Nikola; Zimbakov, Zhan (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
Carotid near-occlusion stenosis is distal luminal collapse of the internal carotid artery beyond a tight stenosis. In everyday practice, it is easily misdiagnosed as a conventional high degree stenosis. Because of the different stroke risk, proper differentiation of these two types of lesions is important for the correct treatment decision. Recent data showed no advantage of best medical therapy versus surgical endarterectomy or carotid artery stenting.We report a case of carotid artery stenting of symptomatic ICANO stenosis without full collapse, via transradial approach, in the presence of contralateral ICA (Internal Carotid Artery) â€œcriticalâ€ stenosis.This case provides additional data about optimal treatment of these patients, who are often excluded from randomized control trials (RCTâ€™s), but frequently encountered in the cardiovascular practice. Key words: carotid artery stenting, near occlusion stenosis, internal carotid artery https://doi.org/10.55302/JMS2141145b